Thin Films of Poly(Ionic Liquids) Containing L-Alanine and L-Serine Amino Acids for Immobilization of Laccase - Pavez-Irrazabal, J; Pavez-Irrazabal, J; Escrig-Murua, J; Silva-Molina, C; Silva-Molina, C (American Chemical Society, 2025)
Recently, poly(ionic liquid)s (PILs) have emerged as a family of polymeric materials that are being increasingly investigated for interdisciplinary applications. PILs as matrices for the immobilization of enzymes have gained greater attention. PILs with amino acid counterions could contribute not only to produce more biocompatible films for immobilization but also to maintain their enzymatic activity. Moreover, the surface properties are factors governing enzyme adsorption. Laccases are popular enzymes, because of their ability to remove dyes and other pollutants in an environmentally friendly way. In this study, we present the synthesis and characterization of thin films of PILs that incorporate two different amino acids as counterions, designed to immobilize and assess the enzymatic activity of Laccase. To investigate the influence of polarity and to modulate the hydrophobic and hydrophilic properties of these films, we selected l-alanine as a nonpolar amino acid and l-serine as a polar counterpart. We will evaluate the activity of laccase immobilized on PIL-modified surfaces by using bromothymol blue (BTB) dye. The PIL-Ser film exhibited larger globular structures, likely resulting from the formation of small island-like aggregates or clusters. In contrast, the PIL-Ala film displayed more uniform interconnected globular structures with more regular and slightly homogeneous morphology. The findings from AFM were consistent with the observations made through FE-SEM. The PIL-Ser films were highly hydrophilic, exposing polar amino acid residues to air when adsorbed onto a silicon surface, whereas the PIL-Ala films primarily presented nonpolar groups at the interface. The amount of adsorbed Laccase was shown to be dependent on the nature of the amino acid residue present in the PIL, being almost doubled in the case of PIL-Ser. In conclusion, regardless of the amount of Laccase immobilized on the PIL-Ser and PIL-Ala films, both types of films demonstrated effective support for the degradation of BTB dye. © 2025 American Chemical Society.